Schizophrenia: a disorder of intersubjectivity: a phenomenological analysis - Van Duppen, Zeno (2016)
This dissertation combines two scientific disciplines and research fields, namely philosophy and psychopathology. Within such a wide field of investigation, two precise perspectives are to be adopted in this inquiry: stemming from the first field, the phenomenological perspective on subjectivity and intersubjectivity; stemming from the second, the psychopathological perspective on schizophrenia. The combination of philosophy and psychopathology has often proven fruitful. Moreover, the main motivation for such combined approach is justified by the strong belief that, when critically used, phenomenology offers a viable method of studying the first-personal perspective of experience, including the experiences of people with mental disorders. Philosophical analysis can thereby be used as a means to evaluate the meaning and adequacy of psychopathological concepts and ideas. As a result, phenomenological psychopathology may help understand what is often claimed to be incomprehensible. Particularly for the understanding of schizophrenia, this is taken to be a valuable contribution. For more than twenty years now, the phenomenological approach to schizophrenia has developed a strong and influential hypothesis on the basic alterations of this disorder. Schizophrenia, it is claimed, is a disorder of subjectivity, and more specifically, a disorder of the minimal self. Simultaneously, and often in conjunction, philosophical research on the self has vastly proliferated. The vivid interaction between these two fields makes the phenomenology of schizophrenia a good example of effective interdisciplinary work. Within the philosophical debate on subjectivity, intersubjectivity, or the relation between self and other, is currently a key topic. However, this has not significantly influenced the psychopathology of schizophrenia yet. The initial and fundamental claim of this dissertation is indeed that a renewed evaluation and inclusion of intersubjectivity, next to subjectivity, is to increase the validity of the phenomenological approach to schizophrenia. This would allow the previous hypothesis on schizophrenia as minimal self disorder to be challenged, criticized, or complemented, which would accordingly increase the significance and its clinical value. What I will attempt to do in this dissertation is then to thoroughly evaluate the role of intersubjectivity in schizophrenia. It will hence become clear what this role and its significance are. Consequently, I will finally argue that the basic alterations of schizophrenia concern both subjectivity and intersubjectivity. My argument is developed in four chapters. In the first, I introduce the topic of the self, including the distinction between the minimal and the extended self. This chapter equally introduces schizophrenia as a psychiatric concept, and three different clinical approaches are discussed, among which the phenomenological approach in most detail. After the topics of the self and schizophrenia, I introduce intersubjectivity, notably from a developmental-psychological perspective. By way of status quaestionis, I recapitulate the current research on intersubjectivity and schizophrenia. It will become clear that this research is relatively scarce. I then conclude the chapter with a full formulation of the two research questions informing this dissertation, namely Is schizophrenia an intersubjectivity-disorder? and Which self-concept is suited to define schizophrenia as a self and intersubjectivity disorder? The second chapter examines the phenomenology of intersubjectivity. The exact delineation of what is meant here by intersubjectivity will allow the reader to acknowledge its extent and variety. This chapter is aimed to provide the necessary philosophical tools to analyse schizophrenia in the light of intersubjectivity. In the third chapter I turn to psychopathology. In the first section, I analyse the work of seven major psychopathologists on schizophrenia. The goal of this section is to look for elements of intersubjectivity in their accounts of schizophrenia. Many of these psychopathologists have been influential for the development of the current self-disorder hypothesis, and the investigation intends to show how some crucial intersubjective elements in their work have been neglected. In the second section of this chapter, I focus on the symptoms, signs, and phenomena of schizophrenia that relate to intersubjectivity. This chapter finally offers all the material needed to positively answer the first research question. In the fourth chapter, I bring together psychopathology and philosophy, and I attempt to answer the two research questions. Since Chapter 3 allows me to affirmatively answer the first question, I examine whether the current self-disorder hypothesis is adequate to integrate intersubjectivity disturbances. It will appear that it is not, and the first section of this chapter consequently deals with the question why intersubjectivity and its disturbances have been neglected until now. In the second section it will become clear that no different self-concept is required, but that schizophrenia primarily concerns a particular capacity or orientation of subjectivity. I introduce the concept of open subjectivity and thereby answer the second research question. By describing schizophrenia as a disturbance of open subjectivity, I am finally able to integrate both self-disturbances and intersubjectivity-disturbances into a coherent and unified theory. To conclude this dissertation, I summarize and recapitulate its major issues, questions, and results in Chapter 5. Both clinical implications and possible future research are also discussed here.